Biochemical properties, enterohaemolysin production and plasmid carriage of Shiga toxin-producing Escherichia coli strains - Souza, Mario R.S.R.S.M; Klassen, Giseli; De Toni, Fabiana; Rigo, Liu U; Henkes, Caroline; Pigatto, Caroline P; Dalagassa, Cibelle de Borba; Fadel-Picheth, Cyntia M.T (Memórias do Instituto Oswaldo Cruz, 2010)
Thirty-eight strains of Shiga toxin-producing Escherichia coli (STEC) were characterised in terms of biochemical properties, enterohaemolysin production and plasmid carriage. A wide variation in the biochemical properties was observed among the STEC, with 14 distinct biotypes identified. Biotype 1 was the most common, found in 29% of the strains. Enterohaemolysin production was detected in 29% of the strains. Most of the bacterial strains (95%) carried one or more plasmids and considerable heterogeneity in size and combinations was observed. Seven distinct plasmid profiles were identified. The most common profile, characterised by the presence of a single plasmid of ~90 kb, was found in 50% of these strains. These data indicate extensive diversity among STEC strains. No correlation was found among biotype, serotype, enterohaemolysin production and plasmid profile.